Meningkatkan Hasil Belajar Pendidikan Pancasila Siswa Melalui Model Kooperatif Tipe Student Teams Achievement Division Berbantuan Media Quartet Card - Aulia Fahsa; Nina Nurhasanah; Iva Sarifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The learning outcomes of Pancasila Education students are still relatively low, especially in the cognitive realm. This is characterized by students' difficulties in understanding the material. This research aims to improve the learning outcomes of Pancasila Education students through a Cooperative learning model of the Student Teams Achievement Division type with the help of Quartet Card media. The results showed an increase in learning outcomes with a percentage of cycle I (64.5%) and cycle II (93.5%). This increase shows that the actions implemented are able to improve the learning outcomes of Pancasila Education students. Based on these results, it can be concluded that the learning model applied is able to improve the learning outcomes of Pancasila Education students.